UNMASKING SILENT MYOCARDIAL INFARCTIONS WITH A SMARTWATCH - Danielle De Greef, DO (Elsevier, 2024)
Therapeutic Area: CVD Prevention - Primary and Secondary Case Presentation: A 70-year-old male with a history of HTN, HLD, CAD s/p PCI with DES x2 to LAD and DES x2 to RCA, squamous cell carcinoma, and a prior silent MI discovered incidentally while undergoing clearance for a hernia repair presents with the complaint of tachycardia detected by his watch. He is asymptomatic. Initial EKG was significant for atrial fibrillation with RVR with a troponin of 0.1. Repeat EKG revealed lateral ST segment depressions. Serial troponins remained elevated with a peak troponin of 0.68. Left heart catheterization showed critical left main disease, moderate proximal LAD stenosis, and total occlusion of the proximal RCA. A successful emergency CABGx3 was performed. Background: Myocardial infarction (MI) is a leading global cause of mortality. Patients with silent myocardial infarction (SMI) typically exhibit minimal to no symptoms and therefore often neglect medical attention. SMI encompasses three types:1. Type I: The least frequent, occurring in asymptomatic patients with severe coronary artery disease (CAD) devoid of anginal symptoms.2. Type II: Present in individuals with documented prior MI3. Type III: The most prevalent, manifesting in patients with various forms of angina (1).Risk factors for SMI include smoking, familial heart disease, hypercholesterolemia, hypertension, diabetes, and obesity (2). SMI is a predictor of unfavorable long-term outcomes, with more than a threefold increase in mortality and major adverse cardiovascular events (MACE) (4). It accounts for up to 54% of all MIs in the general population (4). We present the case of a 70-year-old male incidentally diagnosed with SMI during an episode of tachyarrhythmia culminating in coronary artery bypass grafting (CABG). Conclusions: The increased mortality and MACE associated with SMIs is a significant factor to consider in addressing the importance of secondary prevention strategies. There are currently no universal evidence-based screening recommendations due to the lack of consensus regarding effectiveness and cost-efficiency methods as well as the risks and benefits regarding screenings. Therefore, considering patient comorbidities and a history of SMI are critical in preventing SMI due to the increased incidence associated with new coronary events while a more effective screening approach is encouraged (2,6).